How U.S. Multinational Corporations, Unions, and Government View Each other and the Direction of U.S. Policies - Root, Franklin R.; Mennis, Bernard (Journal of International Business Studies, 1976)
This article reports on the findings of field interviews with officials of MNCs, unions, and the U.S. government. The findings delineate perceptual gaps among the three groups that, in particular, thwart any meaningful union/MNC and union/government dialogues.